Autocrine effects of transgenic resistin reduce palmitate and glucose oxidation in brown adipose tissue - Pravenec, Michal; Mlejnek, Petr; Zídek, Václav; Landa, Vladimír; Šimáková, Miroslava; Šilhavý, Jan; Strnad, Hynek; Eigner, Sebastian; Eigner Henke, Kateřina; Škop, Vojtěch; Malínská, Hana; Trnovská, Jaroslava; et al. (Physiological genomics, 2016)
Resistin has been originally identified as an adipokine that links obesity to insulin resistance in mice. In our previous studies in spontaneously hypertensive rats (SHR) expressing a nonsecreted form of mouse resistin (Retn) transgene specifically in adipose tissue (SHR-Retn), we have observed an increased lipolysis and serum free fatty acids, ectopic fat accumulation in muscles, and insulin resistance. Recently, brown adipose tissue (BAT) has been suggested to play an important role in the pathogenesis of metabolic disturbances. In the current study, we have analyzed autocrine effects of transgenic resistin on BAT glucose and lipid metabolism and mitochondrial function in the SHR-Retn vs. nontransgenic SHR controls. We observed that interscapular BAT isolated from SHR-Retn transgenic rats compared with SHR controls showed a lower relative weight (0.71 ± 0.05 vs. 0.91 ± 0.08 g/100 g body wt, P < 0.05), significantly reduced both basal and insulin stimulated incorporation of palmitate into BAT lipids (658 ± 50 vs. 856 ± 45 and 864 ± 47 vs. 1,086 ± 35 nmol/g/2 h, P ≤ 0.01, respectively), and significantly decreased palmitate oxidation (37.6 ± 4.5 vs. 57 ± 4.1 nmol/g/2 h, P = 0.007) and glucose oxidation (277 ± 34 vs. 458 ± 38 nmol/g/2 h, P = 0.001). In addition, in vivo microPET imaging revealed significantly reduced (18)F-FDG uptake in BAT induced by exposure to cold in SHR-Retn vs. control SHR (232 ± 19 vs. 334 ± 22 kBq/ml, P < 0.05). Gene expression profiles in BAT identified differentially expressed genes involved in skeletal muscle and connective tissue development, inflammation and MAPK and insulin signaling. These results provide evidence that autocrine effects of resistin attenuate differentiation and activity of BAT and thus may play a role in the pathogenesis of insulin resistance in the rat.
Keywords: kyseliny mastné neesterifikované; Insulin Resistance; Muscle, Skeletal; metabolismus lipidů; Transcriptome; glukosa; Glucose; Mice, Inbred BALB C; Obesity; Fatty Acids, Nonesterified; Rats, Inbred SHR; potkani inbrední SHR; Resistin; inzulin; krysa rodu Rattus; Oxidation-Reduction; Palmitates; autocrine; palmitany; Rats, Transgenic; myši; Autocrine Communication; Mice; inzulinová rezistence; obezita; mitochondrie; Lipid Metabolism; transgenic; Adipose Tissue, Brown; mužské pohlaví; Mitochondria; resistin; potkani transgenní; myši inbrední BALB C; zvířata; autokrinní signalizace; transkriptom; oxidace-redukce; spontaneously hypertensive rat; Rats; Animals; Male; kosterní svaly; hnědá tuková tkáň; Insulin; brown adipose tissue